Capturing everyday experiences of typically developing children aged five to seven years: A feasibility study of experience sampling methodology - Vilaysack, B.; Cordier, Reinie; Doma, K.; Chen, Y. (Wiley-Blackwell Publishing Asia, 2016)
Background: Understanding children's perception of their experiences is imperative for developing client-centred interventions for paediatric populations. However, perceptions of young children in the myriad circumstances that they live in have not yet been properly investigated. Subsequently, this study tested the feasibility and appropriateness of experience sampling method (ESM), an ecological momentary assessment, on typically developing children aged between five and seven years. Methods: Ten children (five boys and five girls) carried an Android© device with a pre-installed ESM survey exploring their everyday life and their perceived internal experiences. Children were asked to respond to the survey eight times daily, at random times generated by the device, for seven days. Results: An acceptable signal response rate (47.6 ± 18.9%) and short average time required for survey completion (83 ± 49 seconds) supported the feasibility of the ESM for use in research with children aged between five and seven years. Children reported the questions were straightforward and survey completion interfered very little with everyday activities, supporting appropriateness of the method. Through graphic analysis we illustrated the usability of ESM for capturing the influence of everyday contexts on perceived internal experiences. Conclusions: The ESM holds promise for examining the impact of environmental context on everyday experiences of young typically developing children.